2012
DOI: 10.1128/iai.05805-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Burkholderia pseudomallei K96243 Capsular Polysaccharide I Coding Region

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis, a disease endemic to regions of Southeast Asia and Northern Australia. Both humans and a range of other animal species are susceptible to melioidosis, and the production of a group 3 polysaccharide capsule in B. pseudomallei is essential for virulence. B. pseudomallei capsular polysaccharide (CPS) I comprises unbranched manno-heptopyranose residues and is encoded by a 34.5-kb locus on chromosome 1. Despite the importance of this locus, the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…The response was greater with a wcbB mutant completely lacking the polymer of unbranched manno-heptopyranose residues than with a wcbN mutant that retains a capsule-specific epitope but whose virulence is attenuated (9). In common with other encapsulated bacterial pathogens, it appears that the B. pseu-…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The response was greater with a wcbB mutant completely lacking the polymer of unbranched manno-heptopyranose residues than with a wcbN mutant that retains a capsule-specific epitope but whose virulence is attenuated (9). In common with other encapsulated bacterial pathogens, it appears that the B. pseu-…”
Section: Discussionmentioning
confidence: 85%
“…4A). In addition, we observed that the amount of extracellular DNA released by human PMNs was significantly higher following infection by a wcbB mutant which lacks capsular polysaccharide I (CPS-I; a chromosome 1-encoded polymer of unbranched manno-heptopyranose residues [9]) than infection by the K96243 parent strain (Fig. 4A).…”
Section: B Pseudomallei-induced Net Formation Requires Nadph Oxidasementioning
confidence: 75%
See 1 more Smart Citation
“…The putative heptose-guanyl transferase WcbM 19,20 shows a strong thermal shift on binding to GTP ( Figure 3A). An initial screen suggested that the K d would be in the range of around 100 µM.…”
Section: Representative Resultsmentioning
confidence: 99%
“…N-Acetylgalactosamine, a derivative of NAGA, has also been documented as one of the basic components for EPS of B. pseudomallei (19). The implications for virulence and immune response of these different biochemical profiles remains uncertain, but it has been suggested that the amount of capsular polysaccharide in B. pseudomallei compared to that in other Burkholderia species may well contribute to its relative virulence (20).…”
mentioning
confidence: 99%